Đào tạo sinh viên sư phạm Ngành Giáo dục thể chất: Góc nhìn từ mô hình TPACK (Tạp chí khoa học Đào tạo và Huấn luyện Thể thao, 2024)
Đào tạo sinh viên sư phạm Ngành Giáo dục thể chất: Góc nhìn từ mô hình TPACK